2016
DOI: 10.1089/ars.2015.6458
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin, a Pleiotropic Protein in Health and Disease

Abstract: The main sources of Lf in human cardiometabolic disorders should be clarified to identify new perspectives for future research and develop new strategies using Lf in therapeutics. Antioxid. Redox Signal. 24, 813-836.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 227 publications
(221 reference statements)
1
85
0
4
Order By: Relevance
“…Lactoferrin [6] is closely related to the plasma iron-carrier protein, transferrin. Unlike transferrin which evolved to deliver iron to cells via the transferrin receptor 1 and releases iron in acidified endosomes at pH below 5.5, lactoferrin does not release its iron even at pH 3.5, a property that assures iron sequestration even in infected tissues where the pH is commonly highly acidic.…”
Section: Lactoferrinmentioning
confidence: 99%
“…Lactoferrin [6] is closely related to the plasma iron-carrier protein, transferrin. Unlike transferrin which evolved to deliver iron to cells via the transferrin receptor 1 and releases iron in acidified endosomes at pH below 5.5, lactoferrin does not release its iron even at pH 3.5, a property that assures iron sequestration even in infected tissues where the pH is commonly highly acidic.…”
Section: Lactoferrinmentioning
confidence: 99%
“…The major medical development of the antimicrobial proteins reviewed here appears to be lactoferrin, which, as described above, is an iron binding protein but, like LL-37, is pleiotropic and also displays a broad range of antimicrobial activity using a number of mechanisms, which includes the release of derivative AMPs via hydrolysis by proteases [162,270,271]. Lactoferrin and its related peptides shows the potential for a number of clinical uses, ranging from wound healing and the detection of bacteria to the treatment of microbial infections both alone and in combination with other clinically relevant agents [272].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…Neutropenia is defined as a reduction in the absolute number of neutrophils in the blood circulation, predisposing individuals to severe or fatal infections [285], and currently, hLF(1-11) awaits development for the prevention of bacteremia and fungal infections in immunocompromised individuals (Table 2) [273]. Lactoferricin B is cleaved from the N-terminal region of bovine lactoferrin under acid pH conditions and has an extremely wide spectrum of antimicrobial activity against bacterial, fungal and parasite species as well as showing anti-catabolic and anti-inflammatory effects [162,270,271]. Based on these abilities, this peptide has featured in numerous preclinical trials and shows the potential for a variety of therapeutic purposes, including the treatment of ocular infections, osteo-articular gastro-Intestinal and dermatological diseases, along with applications in veterinary practice and the food industry [272].…”
Section: Potential Applications Of Ph Dependent Antimicrobial Peptmentioning
confidence: 99%
“…There are also suggestions that Lf can play a role in the initiation of T-cell activation through the modulation of dendritic cell function [79]. Several studies (mostly on animals but also on humans) have focused on the immunomodulatory effects of orally administered Lf: Mulder et al [80] found that oral administration of bLf to healthy human males increased the activation of total T-cell, helper T-cell and cytotoxic T-cell, increasing also hydrophilic antioxidant capacity (reviewed by Mayeur et al in 2016 [81]).Saraiva et al [82] fed piglets with 3.6 g/L of bLF and showed higher IgG concentrations in serum and more IL-10, an immunomodulatory cytokine potentially limiting inflammation, was secreted by spleen cells into the culture media;Liu et al [83] administering orally bLf to piglets, and found an increase of the blood NK cell populations and NK Lf receptor expression without affecting NK cell cytotoxicity, suggesting that Lf could help protect the organism of infants from infections;Cooper et al [84] fed young pigs with transgenic cows’ milk containing rhLf. They showed favorable changes in systemic health in rhLf-milk fed pigs that had beneficial changes in circulating leukocyte populations with a decrease in neutrophils and increase in lymphocytes which is an indicator of decreased systemic inflammation.…”
Section: Nutraceutical and Immunomodulation Protective Effectsmentioning
confidence: 99%
“…Mulder et al [80] found that oral administration of bLf to healthy human males increased the activation of total T-cell, helper T-cell and cytotoxic T-cell, increasing also hydrophilic antioxidant capacity (reviewed by Mayeur et al in 2016 [81]).…”
Section: Nutraceutical and Immunomodulation Protective Effectsmentioning
confidence: 99%